The impact of anger on creative process engagement: the role of social contexts - Costa, C. G.; Zhou, Q.; Ferreira, A. I. (Journal of Organizational Behavior, 2018)
Drawing on the cognitive persistence perspective of creativity and conservation of resources theory, we investigated how 2 social contexts (perceived relationship conflict and coworker support for creativity) influence the relationship between anger and creative process engagement (CPE) in organizations. We tested our hypotheses using 422 daily surveys from 98 participants, collected over 5 consecutive workdays. The results show that anger perceived relationship conflict and coworker support for creativity interact to influence CPE. Specifically, when relationship conflict is high, the anger–CPE relationship is positive for employees who receive high coworker support for creativity, but negative for those who receive low coworker support for creativity. In contrast, when relationship conflict is low, the anger–CPE relationship is positive but does not differ at high versus low coworker support for creativity.